2021
DOI: 10.3390/e23121627
|View full text |Cite
|
Sign up to set email alerts
|

Battery Charging in Collision Models with Bayesian Risk Strategies

Abstract: We constructed a collision model where measurements in the system, together with a Bayesian decision rule, are used to classify the incoming ancillas as having either high or low ergotropy (maximum extractable work). The former are allowed to leave, while the latter are redirected for further processing, aimed at increasing their ergotropy further. The ancillas play the role of a quantum battery, and the collision model, therefore, implements a Maxwell demon. To make the process autonomous and with a well-defi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…For thermal maps H 0 = H S , and Eq. (18) gives p (L) w (x) = δ(x). The external agent is truly passive.…”
Section: B Fluctuations In the Equilibrium Statementioning
confidence: 99%
See 1 more Smart Citation
“…For thermal maps H 0 = H S , and Eq. (18) gives p (L) w (x) = δ(x). The external agent is truly passive.…”
Section: B Fluctuations In the Equilibrium Statementioning
confidence: 99%
“…INTRODUCTIONRepeated interaction schemes, a.k.a collisional models [1-6], have played a vital role in the development of quantum optics [7-10] and the rapid evolution of quantum thermodynamics [11][12][13][14][15]. The idealized and straightforward formalism has been crucial to designing and understanding quantum devices such as information engines [16][17][18][19], heat engines [12,[20][21][22][23], and quantum batteries [24][25][26][27][28][29][30][31][32][33]. Recently, it was realized that the framework can be extended to deal with macroscopic reservoirs [23,34], expanding the reach of applications in quantum thermodynamics.…”
mentioning
confidence: 99%
“…In such collective processes, the role of dissipation [46][47][48][49][50][51][52], many-body interactions [44,[53][54][55][56][57][58][59][60][61][62][63], and energy fluctuations [64][65][66][67][68][69][70] has also been investigated. In parallel, various types of quantum systems have been considered as quantum batteries, ranging from qubit ensembles [42,[71][72][73][74][75][76][77][78] and ladder models [67,[79][80][81][82][83][84] to oscillators and flywheels [50,[85][86][87][88]. One of the prime candidates for experimental proofs-of-principle is the Dicke-model battery [71]…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, if the system collides with environmental particles that contain the history of the information, the dynamics is considered to be non-Markovian. Apart from works investigating non-Markovian dynamics [40][41][42][43][44][45][46][47][48][49][50][51], CM was also used to study quantum synchronization [52], quantum steering [53], multipartite dynamics [54], multipartite entanglement generation [55], quantum friction [56], and thermodynamics [57][58][59][60][61], in particular for quantum thermometry [62,63]. A comprehensive panorama of studies on CM can be found in [64].…”
Section: Introductionmentioning
confidence: 99%